2012
DOI: 10.1161/circulationaha.111.045146
|View full text |Cite
|
Sign up to set email alerts
|

Human Embryonic and Induced Pluripotent Stem Cell–Derived Cardiomyocytes Exhibit Beat Rate Variability and Power-Law Behavior

Abstract: Background-The sinoatrial node is the main impulse-generating tissue in the heart. Atrioventricular conduction block and arrhythmias caused by sinoatrial node dysfunction are clinically important and generally treated with electronic pacemakers. Although an excellent solution, electronic pacemakers incorporate limitations that have stimulated research on biological pacing. To assess the suitability of potential biological pacemakers, we tested the hypothesis that the spontaneous electric activity of human embr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
93
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(106 citation statements)
references
References 39 publications
(64 reference statements)
12
93
0
1
Order By: Relevance
“…This technique has been extended to human cells [36,37]. Mandel et al used the patient's own hair to generate cardiomyocytes from iPSC and showed that these cells were spontaneously active with intrinsic heart rate variability and ability to respond to isoprenaline and carbamylcholine [38].…”
Section: Cell-based Approachmentioning
confidence: 99%
“…This technique has been extended to human cells [36,37]. Mandel et al used the patient's own hair to generate cardiomyocytes from iPSC and showed that these cells were spontaneously active with intrinsic heart rate variability and ability to respond to isoprenaline and carbamylcholine [38].…”
Section: Cell-based Approachmentioning
confidence: 99%
“…En términos amplios, podemos clasificar las células madre según su potencialidad en células madre pluripotenciales (embrionarias o inducidas) y multipotenciales (adultas). Un creciente volumen de evidencia preclínica, avala el gran potencial terapéutico de las células madre pluripotenciales inducidas (iPSC) en patología cardiovascular [9][10][11] . Existen sin embargo, dudas razonables respecto a su eventual efecto tumorigénico y/o inmunogénico, lo que ha dificultado por ahora su traslado a la clínica 12,13 .…”
Section: Tipos Y Fuentes De Células Madre En Cardiologíaunclassified
“…Second, such a preparation might provide an ideal source with which to create a "biological pacemaker" to replace current electronic pacemakers in treating rhythm disorders. Proof-of-concept experiments with biologic pacemakers have demonstrated some success with the implantation of fetal (Ruhparwar et al, 2002) or adult ) SAN cells and beating embryoid bodies (EBs) derived from embryonic stem cells (ESCs) Xue et al, 2005); cardiomyocytes from induced pluripotent stem cells (iPSCs) also have been produced and characterized (Novak et al, 2010;Mandel et al, 2012) but not yet implanted to form a biologic pacemaker. In addition, adult mesenchymal stem cells, not driven down a cardiac lineage but genetically modified to generate a pacemaker current (I f ), have also proven successful (Potapova et al, 2004;Rosen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%